2023
DOI: 10.1155/2023/2586372
|View full text |Cite
|
Sign up to set email alerts
|

How Do Vehicles Make Decisions during Implementation Period of Discretionary Lane Change? A Data-Driven Research

Abstract: To investigate and compare the lane changing behavior of passenger cars and heavy vehicles during the implementation period (defined as the interval from the start time to the end time of a lane change maneuver), this study applies the gradient boosting decision tree (GBDT) method to model the lane changing behavior of heavy vehicles and passenger cars, respectively. Results show that the lane change models vary with the vehicle types and lane change directions. Different factors are considered by the drivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…One of the personalization measures is to simulate human driving behavior by switching to the appropriate driving style in certain scenarios. In the mixed driving environment, simulating human behavior for AVs can make driving behavior on the road more consistent, leading to safer driving and fewer crashes [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the personalization measures is to simulate human driving behavior by switching to the appropriate driving style in certain scenarios. In the mixed driving environment, simulating human behavior for AVs can make driving behavior on the road more consistent, leading to safer driving and fewer crashes [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, French et al [8] found that dangerous driving styles are associated with serious trafc crashes. Generally, aberrant driving style recognition has several potential applications in practice as follows: (1) helping trafc managers analyze driving behaviors and the contributing factors of road crashes and identify driving risks in a timely manner, (2) enabling AVs to take timely measures to avoid conficts with aberrant-style driving and potentially dangerous vehicles, and (3) assisting trafc managers in taking preventive measures for certain accidents in advance to improve trafc efciency and trafc safety. Terefore, studies on recognizing driving styles and extracting aberrant ones are of great importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation